Impact of smart technology use on sleep quality in individuals with autism spectrum disorder: a mixed-methods investigation - Abouzed, Mohamed; Salama, Basem; Gabr, Amgad; Elag, Khaled A.; Soliman, Mahmoud; Elsaadouni, Nisrin; Elzahab, Nasr Abou (Frontiers in Psychiatry, 2024)
Background Sleep disturbances are common among individuals with autism spectrum disorder (ASD) and can have a negative impact on their daily functioning and core symptoms. As the use of smart technologies continues to rise, it is crucial to understand how these devices affect the sleep quality of individuals with ASD. Aim The objective of this study was to examine the relationship between the use of smart technology and sleep quality in individuals with ASD. Methods A mixed-methods approach was employed, combining both quantitative and qualitative data collection techniques. A sample of 83 individuals with ASD, aged between 8 and 25 years, assessed their sleep quality using the Pittsburgh Sleep Quality Index. Additionally, information regarding patterns of smart technology use and relevant covariates was collected. Correlation and regression analyses were conducted to analyze the data. Furthermore, semi-structured interviews were conducted with a subset of participants and their caregivers. Results Significant positive correlations were found between poorer sleep quality scores and total screen time (r = 0.42, p < 0.001), pre-bedtime technology use (r = 0.51, p < 0.001), gaming (r = 0.32, p = 0.003), and social media use (r = 0.29, p = 0.008). Pre-bedtime technology use was a significant predictor of poorer sleep quality (β = 0.32, p = 0.006), even after controlling for age, gender, and ASD severity. Conclusion The findings of this study emphasize the significant associations between the use of smart technology, particularly before bedtime, and poorer sleep quality in individuals with ASD. These results underscore the importance of developing evidence-based interventions and guidelines to promote healthy sleep habits and mitigate the negative effects of technology exposure in this population.